Reliability analysis of autonomous measuring equipment for seamless steel pipes in production lines of a steel industry: focus on maintenance centered on reliability and cost reduction - de Paula, Fernando Augusto Baia (Brazilian Journal of Production Engineering, 2024)
This study aimed to demonstrate how maintenance focused on process reliability can be beneficial to companies’ productivity. The study was conducted by addressing investigation techniques within the production lines of seamless steel tubes of a Brazilian company located in the city of Jeceaba, Minas Gerais. Calibration tests were performed on the length gauges of the electromagnetic inspection equipment and the tube cutting saws of the seamless steel tube production process, mitigating failures and determining safe parameters for measuring the tubes produced by the company, making the results more reliable and enabling a reduction in production costs. The study arose within the intern development program promoted by the company, which consisted of a series of activities to be developed by the interns to improve internal processes and reduce costs in the company’s production process. Given the work developed, it was possible to discover a cost reduction of approximately R1 million per year in the process, optimizing the process and the companies’ profits.